El uso de otolitos y huesos de la cabeza para la identificación de dos especies del género Merluccius, en estudios de predador-presa - Delpiani, Sergio Matias (2012)
A comparative osteological analysis of six bones and the sagitta otolith in Merluccius hubbsi and M. australis, two species that live in Southwest Atlantic, has been carried out. The objective was to contribute to identifying these two species as prey in the diet studies, and further description of these bony elements for a better taxonomic identification. Fresh bones disarticulation techniques were used. Potentially diagnostic features were observed for discrimination of species in the following elements: urohyal, maxilla, premaxilla, dentary, quadrate, hyomandibular, and the sagitta otolith.